PENGARUH BRAND EVALUATION, TRUST, SATISFACTION, BRAND RELATIONSHIP, BRAND AFFECT, DAN BRAND IMAGE TERHADAP BRAND LOYALTY SABUN MANDI ANTISEPTIK - TANIA TOVIANI; IRMA SATYA INDRIYANTI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The purpose of this study was to determine the effects of Brand Evaluation, Trust, Satisfaction, Brand Relationship, Brand Affect, and Brand Image to Brand Loyalty of Dettol Antiseptic Body Wash at Carrefour South Jakarta. Data were taken from questioner. Samples were selected based on purposive sampling method. Only certain sample met the criteria and can be used as the sample. For this study, multiple regresionis used to find out the effects of all independent variable above to dependent variable. The research showed that Trust, Satisfaction, Brand Affect, and Brand Image had effect to Brand Loyalty of Body Wash Antiseptic. Whereas the variable Brand Evaluation and Brand Relationship had no effect to Brand Loyalty of Body Wash Antiseptic.